Perception of quality of life of a group of individuals subjected to bariatric surgery (2014)
ABSTRACT: The study sought to identify the state of health andquality of life of post-bariatric surgery patients. Methodology.This was a cross-sectional study conducted in 2012 with theparticipation of 338 individuals attending the private practice ofa bariatric surgeon from Medellín (Colombia). With prior signedinformed consent, the survey was filled out by each patient. Theinformation gathered was sociodemographic in nature along withthe World Health Organization’s Quality of Life Brief Questionnaire(WHOQoL-Bref). Results. It was found that 82.2% were womenand mean age was 41±12 years. Gastric bypass was practicedon 79.6% of the cases. Mean weight before surgery was106.3±17.5 Kg and after surgery it was 73.2±13.4 Kg. Nineof every 10 participants classified their quality of life and state ofhealth between extremely well and quite well. Quality of life wasbetter in men, in those younger than 40 years of age, in those fromsocio-economic levels 4 to 6, and in those with educational levelabove the secondary (high school). Conclusion. As a consequenceof the important and rapid weight loss occurring during the firstmonths after surgery, most of the participants perceived havinga good quality of life and were satisfied with their health status.For nursing, it is a challenge to implement educational programsand projects, bearing in mind the sociocultural diversity of theindividuals and communities, through interdisciplinary andinter-sector work, which contributes to the well-being of obeseindividuals subjected to bariatric surgery and their families